Knowledge discovery, knowledge engineering and knowledge management : 5th International Joint Conference, IC3K 2013, Vilamoura, Portugal, September 19-22, 2013. Revised selected papers /: 5th International Joint Conference, IC3K 2013, Vilamoura, Portugal, September 19-22, 2013. Revised selected papers. (2015) - Unknown
No abstract available